Pengaruh Metode Pencampuran Coupling Agent Terhadap Sitotoksisitas Komposit Serat Selulosa Sabut Kelapa / Coir - Cevanti, Twi Agnita; Prananingrum, Widyasri; Soesilo, Diana (Jurnal Material Kedokteran Gigi, 2022)
Research about cellulose fiber from coconut fibers (Cocos nucifera L/coir) was currently done as an organic fillers for dental composite materials. DGEBA was chosen as a coupling agent to obtain covalent chemical bonds between BisGMA, TEDGMA matrices and coir cellulose fibers. The mixing method of DGEBA played an important role in the biocompatibility of the material. The ideal requirement for dental materials must be non-toxic through cytotoxicity tests. Objective to modify the synthesis method of coir-based cellulose as a natural fiber to optimize chemical bonding through polymerization reaction between fiber, coupling agent and matrix. Methods: There were 2 kinds of cellulose synthesis methods, which were (1) synthesis of cellulose solution using DGEBA and ethanol, (2) synthesis of cellulose solution using ethanol without DGEBA. Cytotoxicity test on pulp fibroblast cells with MTT Assay method on coir cellulose fiber composite samples from the two methods. Method 1 cell viability rate for 7 days immersion was 93.30855%, 14 days was 99.07063%, 21 days was 74.53532%. Method 2 obtained 64.68401% for 7 days immersion, 73.79182% for 14 days and 53.15985% for 21 days. Conclusion, the cellulose solution synthesis method using DGEBA and ethanol produces composites with better chemical bonds seen from the results of the cytotoxicity test